Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO298 - Achterberg, Eric Pieter; Schumacher, Mia (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV SONNE during cruise SO298 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 14.04.2023 - 02.06.2023 from Guayaquil (Ecuador) – Townsville (Australia) in the central Pacific Ocean. The main scientific aim of SO298 is to establish the distributions of trace elements and their isotopes (TEIs), quantify their sources from the four major ocean boundaries (rivers, atmosphere, exchange with sediments, ocean crust), and determine their biogeochemical cycling and relationships to large scale ocean circulation along a cruise track in the Equatorial Pacific Ocean (EPO). Data were recorded within the EEZs of Ecuador, Kiribati, Jarvis Island, Howland Island and Baker Island as well as outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Acquisition and provision of the data are part of the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder